Antibacterial potential of silver nanoparticles biosynthesised using Canarium ovatum leaves extract. Issue 5 (24th March 2017) - Arya, Geeta; Kumar, Nitin; Gupta, Nidhi; Kumar, Ajeet; Nimesh, Surendra
Abstract : Silver nanoparticles (AgNPs) have been extensively used as antibacterial agents, owing to their ease of preparation. In the present study, leaves extract of Canarium ovatum have been employed for the biosynthesis of silver nanoparticles (CO‐AgNPs). CO‐AgNPs were synthesised under very mild, eco‐friendly manner where the plant extract acted both as reducing and capping agent. These AgNPs were synthesised by taking into account several parameters, that included, time of reaction, concentration of AgNO3, amount of extract and temperature of reaction. The optimisation studies suggested efficient synthesis of CO‐AgNPs at 25°C when 1.5 mM AgNO3 was reduced with 1:20 ratio of plant extract for 40 min. Size determination studies done on dynamic light scattering and scanning electron microscope suggested of spherical shape nanoparticles of size 119.7 ± 7 nm and 50–80 nm, respectively. Further, characterisations were done by Fourier transform infrared and energy‐dispersive X‐ray spectroscopy to evaluate the functional groups and the purity of CO‐AgNPs. The antibacterial efficacy of CO‐AgNPs was determined against the bacterial strain Pseudomonas aeruginosa . As evident from disc diffusion method studies, CO‐AgNPs remarkably inhibited the growth of the tested microorganism. This study suggested that C. ovatum extract efficiently synthesises CO‐AgNPs with significant antibacterial properties and can be good candidates for therapeutics.